Bioactive Compounds of Fruit Parts of Three Eugenia uniflora Biotypes in Four Ripening Stages - Santos, Suzana C.; Pereira, Marx O. A.; Santos, Karoline B.; Ferri, Pedro H. (Chemistry & biodiversity, 2021)
Variability of secondary metabolites in edible (peel and pulp) and inedible (seeds) parts of three pitanga varieties, red, red‐orange and purple, was investigated during the maturation process. Hydrolysable tannins, anthocyanins, and flavonoids were quantified by HPLC/DAD and carotenoids by absorbance. Peel/pulp showed greater complexity of constituents (carotenoids, anthocyanins, flavonoids, and hydrolysable tannins), while only tannins were identified in seeds, but in quantities of 10 to 100 times greater. The red‐orange variety showed the highest levels of phenolic compounds in seeds and peel/pulp, except anthocyanins. The analysis of the principal response curves showed that the pitanga biotype has greater influence on metabolite variation than ripening stages. During peel/pulp maturation, a reduction in the levels of flavonoids and tannins contrasted with an increase in carotenoids and cyanidin‐3‐O‐glucoside in all varieties, whereas in the seeds oenothein B, the major tannin, increased up to 1.32 g/100 g fresh weight. Such marked differences between fruit parts demonstrate that the seeds in stages E3 and E4 are a source of hydrolysable tannins, compounds known for their antitumor activity, while peel/pulp of all varieties in the ripe stage provide natural antioxidants, such as carotenoids and flavonoids. Lastly, the purple biotype can be a rich source of the cyanidin‐3‐O‐glucoside pigment a potent bioactive compound.